2021
DOI: 10.31004/cendekia.v5i1.430
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Video Pembelajaran Berbantuan Geogebra untuk Meningkatkan Kemandirian Belajar Siswa

Abstract: Saat situasi pandemi Covid–19 seperti sekarang ini, diperlukan media pembelajaran yang mampu meningkatkan kemandirian belajar siswa. Adanya keterbatasan jarak, waktu, dan tempat menuntut guru untuk kreatif dalam membuat media pembelajaran. Salah satunya menggunakan video pembelajaran berbantuan geogebra. Penelitian ini berbeda dari penelitian sebelumnya. Video pembelajaran berbantuan geogebra ini dibuat untuk meningkatkan kemandirian belajar siswa dalam memahami dan menyelesaikan soal–soal persamaan garis luru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
25

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 11 publications
2
23
0
25
Order By: Relevance
“…Learning media and providing a stimulus to motivation and learning outcomes can increase students' independence. Learning videos are effectively used as a tool in the implementation of learning to increase students' independence (Nuritha & Tsurayya, 2021). This is in accordance with research conducted by Novita et al (2019), which mentions that video learning media has a positive and significant influence in improving student learning outcomes.…”
Section: Resultssupporting
confidence: 85%
“…Learning media and providing a stimulus to motivation and learning outcomes can increase students' independence. Learning videos are effectively used as a tool in the implementation of learning to increase students' independence (Nuritha & Tsurayya, 2021). This is in accordance with research conducted by Novita et al (2019), which mentions that video learning media has a positive and significant influence in improving student learning outcomes.…”
Section: Resultssupporting
confidence: 85%
“…The existence of video media is feasible to use and can improve elementary school learning outcomes. This is evident from research it can be concluded that the learning videos that have been developed are worthy of further testing to see the effectiveness in learning (Mutia et al, 2018), which shows that character education-oriented learning videos are effective in improving learning outcomes (Wisada et al, 2019), learning videos are feasible to use in the learning process (Yudiyanto et al, 2020), learning videos can help students understand algebraic structure material (Aziz, 2020), because it contains cooperative learning methods, research conducted by (Yuanta, 2019) it can be concluded that the development of this learning video media is effective for use in the learning process, research conducted by (Ilsa et al, 2020) which shows that the learning video is valid, practical and effective, research conducted by (Ariani et al, 2020) which shows that social studies learning videos containing tests for fifth grade elementary school students are valid and reliable, and research conducted by (Nuritha & Tsurayya, 2021) which shows that learning videos are effectively used as media or student aids in learning mathematics that can increase Student learning independence.…”
Section: Introductionmentioning
confidence: 99%
“…Learning videos can optimize active learning for students and provide great variability in terms of image quality of in-plane objects and movement artifacts (Hong et al, 2021;Ilsa et al, 2020;Kawka et al, 2021). Learning videos can help to understand the learning material and repeat the material if you forget (Nuritha & Tsurayya, 2021). Learning videos are appropriate if used in science learning, especially in the water cycle process, because the teacher may not clearly describe the cycle process.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers can easily spread the developed learning videos into social networks such as Google Drive, Facebook, Blog, YouTube, and many others (Astuti and Febrian 2019). Some research results show that students are more interested in learning using video rather than texts and still images (Purwanti 2015;Purwanto and Rizki 2015;Nuritha and Tsurayya 2021). Therefore, instructional videos are expected to improve students' mathematical problem solving abilities.…”
Section: Introductionmentioning
confidence: 99%